Being “Nutritionally at Risk”: Its Effect on Health Expenses and Length of Hospital Stay: Nutritional Risk: Health Expenses and Length of Hospital Stay - Güngör, Anıl Evrim; Kılınç, Fatma Nişancı; Alparslan, İrem; Çakır, Biriz; Asil, Esma; Esatoğlu, A. Ezel; Yavuz, Yasemin; Demirer, Seher (Progress in Nutrition, 2022)
Objective: Hospital malnutrition is a critical, cost-increasing public health problem that is common in many countries. The study aimed to evaluate the effect of “being nutritionally at risk” on health expenses and length of stay (LOS) in hospital. Material and Method: Nutritional Risk Screening-2002 (NRS-2002) was used to screen 1069 adult patients on admission day. Patients’ anthropometric measurements, unintentional weight loss, hand grip strength (HGS), cancer diagnosis, as well as LOS were recorded. Health expenses for each patient was obtained from hospital billing system. Results: Of the patients, 19.1% had NRS-2002³3 (nutritionally at risk) which was more frequent among male patients (61.8%) than female patients (38.2%) (p